(untitled) (PANGEEA, 2025)
Because of the intense industrial development, the human activity has influenced the environment more and more; recently, more and more negative effects at a global level have been noticed. For this reason, during the recent years the ecological impact of the human activities has been very much emphasized. At present, the majority of the international research programs contain aspects relating to the protection of the environment. This tendency has determined a drastic evaluation of the energy sources. In this context, the new energy sources have begun to have a greater importance. From an ecological point of view, the geothermal energy occupies a favorable place as compared to the majority of the energy sources that are being used at present. The geothermal energy is usually considered to be renewable and sustainable.